EVALUATION OF FORCE DROP-DOWN FOR 50 MM WEB-LASHING USED FOR LOAD SECURING - Jagelčák, Juraj; Saniga, Ján (Doprava a spoje, 2012)
Load securing by web-lashing is a common lashing method to secure a cargo by lashing. The aim of the paper is to study how the tension force is decreasing after the tensioning of the webbing. The paper compares the tensioning with hydraulic piston with the manual tensioning by ratchet tensioners.